Synthesis and properties of spinel phase NdxMg1-xAl2O4 - Ильяслы, Теймур Мамед оглу; Исмаилов, Закир Ислам оглу; Гусейнова, Гумай Алескер гызы; Аббасова, Рена Фридун гызы; Мамедова, Лала Алескер гызы; Вейсова, Ситара Малик гызы (Eastern-European Journal of Enterprise Technologies, 2015)
Crystallization of the amorphous mass and formation of the spinel structure begins at 800 0C. At that, the dimensions of the newly formed crystals are less than 6 nm. Introduction of neodymium has virtually no effect on the crystallographic parameters of pure spinel. Heat-treated samples at 8000C and higher temperatures have mainly a spinel structure. However, in the samples, sintered to 10000C, with the composition Nd0.05Mg0.95Al2O4 and Nd0.1Mg0.9Al2O4, weak unidentified reflexes are revealed. In the heat-treated at 12000C neodymium-doped samples, reflexes only of the spinel structure are observed. The chemical and phase composition of the obtained pigment was examined using various methods, such as thermal analysis (TGA and DTA), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The spectral characteristic of inorganic pigments was studied by infrared spectroscopy (IR), and UV-Vis spectroscopy (200-800 nm).